2019
DOI: 10.1002/ijc.32252
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 induces breast cancer growth through ligand‐independent activation and recruitment of ERα and PRBΔ4 isoform to MYC regulatory sequences

Abstract: Progression to hormone‐independent growth leading to endocrine therapy resistance occurs in a high proportion of patients with estrogen receptor alpha (ERα) and progesterone receptors (PR) positive breast cancer. We and others have previously shown that estrogen‐ and progestin‐induced tumor growth requires ERα and PR interaction at their target genes. Here, we show that fibroblast growth factor 2 (FGF2)‐induces cell proliferation and tumor growth through hormone‐independent ERα and PR activation and their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…7f and g). Interestingly, FGF2 has been widely identi ed as an oncogene to participate in tumorigenesis and metastasis of multiple cancer types [18][19][20]. Thus, we presumed that circ_001422 might contribute to the malignant progression of OS via protecting FGF2 from degradation induced by miR-195-5p.…”
Section: Circ_001422 Positively Regulates Fgf2 Expression In Os Cellsmentioning
confidence: 97%
“…7f and g). Interestingly, FGF2 has been widely identi ed as an oncogene to participate in tumorigenesis and metastasis of multiple cancer types [18][19][20]. Thus, we presumed that circ_001422 might contribute to the malignant progression of OS via protecting FGF2 from degradation induced by miR-195-5p.…”
Section: Circ_001422 Positively Regulates Fgf2 Expression In Os Cellsmentioning
confidence: 97%
“… 652 FGF2 can induce breast cancer growth through ligand-independent activation and stimulate the MYC gene expression through recruitment of ERα and PRB 4 isoform to MYC regulatory sequences. 653 The results from Betsuyaku, T.’s group showed that the FGF2 aptamer that can block FGF2 activity could inhibit the growth of FGF2-FGFR pathway-dependent lung cancer cells. 654 Increased expression of FGF4 in ovarian cancer stem-like cells/cancer-initiating cells is involved in the upregulating tumor initiation capacity of fibroblasts.…”
Section: Fgf Signaling In Tumorsmentioning
confidence: 99%
“…In this way, N-cadherin increases tumor cell interactions with endothelial and mesenchymal cells 25 . On the other hand, broblast growth factor 2 (FGF2) which can induce proliferation of neoplastic cell and tumor hormone-independent growth 30 , is a tumor cell survival factor, which inhibits cell apoptosis through an autocrine secretory loop. In addition, FGF2 can be an activator of angiogenesis during tumor mass growth and metastasis 31 .…”
Section: Discussionmentioning
confidence: 99%